Development of a cooling system for tomato using fuzzy logic approach - Magsumbol, Jo Ann V. (Animo Repository, 2017)
Climate change has great impact in the production of crops worldwide. With the advent of technology, several methods have been developed to adapt to an ever changing world climate. One of these is to provide a microclimate technology that can provide an environment suitable for the growth and development of a plant. Among the growth factors affected by the climate change, temperature plays a very vital role in growing tomato plant and can be controlled through different cooling methods. A temperature which is greater or less than the necessary range for the tomato plant will either lead to immature fruit or loss of flowers. The focus of this research is to monitor and control the temperature inside a growth chamber environment for growing a tomato plant. The input parameters that will be used to monitor and control microclimatic conditions include crop age of the tomato plant, time of the day, and air temperature. Temperature inside the growth chamber will be compared to the temperature outside the growth chamber, as well as to the optimum temperature for the growth stage of the tomato plant. Based on these parameters, fuzzy logic system will be used to make decisions to control the temperature setting of the air-condition unit inside the chamber. © 2017 IEEE.